La gestión de negocio y la promoción del producto. El caso del complejo Rio Chila en Buena Fe- Ecuador, 2020 - Muñoz Barberan, Cristian Manuel (2021)
The present investigation entitled "Business Management and its impact on the Promotion of the services offered by the Río Chila Complex of the Fumisa Parish, year 2020", has the general objective of analyzing the business management in the Río Chila Complex of the Fumisa parish, year 2020. It seeks to propose a Promotion Plan that allows to publicize the services offered by the tourist complex. It is a descriptive field investigation with theoretical foundations consulted in information sources. A survey was conducted of the personnel working in the place and also of people from the Canton Buena Fe, Nueva Zulema, Patricia Pilar and Los Angeles sectors. The questions were designed based on the specific research objectives which allowed obtaining information that revealed the need to use advertising strategies to promote the complex. Various advertising strategies are proposed that will undoubtedly add to a greater promotion of the place, contributing to better business management results. Key Words: Business Management, Promotion Plan, Tourist Complex, Marketing, Services.